IMPLEMENTASI ALGORITMA BREADTH FIRST SEARCH DAN METODE CERTAITY FACTOR PADA SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN CABAI - Ganda Yoga Swara; Minarni; Putri Mandarani; Anisya; Dede Wira Trise Putra (ITP Press, 2021)
Abstract The Department of Agriculture, Food Crops and Horticulture, Regency of Lima Puluh Kota recorded a decrease in chili production every year which can cause direct losses to farmers. This is due to the presence of diseases that can reduce the quantity and quality of yields, increase production costs, and reduce the ability of farming businesses. To overcome this problem, the Department of Agriculture, Food Crops and Horticulture has deployed agricultural extension workers (PPL) as communicators for development who are expected to play multiple roles, as teachers, mentors, advisors, information providers and farmer partners. In Fifty Cities District, the number of existing agricultural extension workers is 104 people. They foster 166,157 farmers with an area of 22,282 ha and plantation area of 28,150 ha who are members of more than 1,400 farmer groups spread over 410 jorong, 79 nagari, and 13 sub-districts in Lima Puluh Kota Regency. Because the extension workers are not comparable with the number of regions, the extension process, the performance of the extension workers, and the knowledge that will be conveyed to farmers are not optimal. Therefore, a system was designed, namely an expert system for diagnosing chili plant diseases using the CF (Certainty Factor) method and the BFS (Breadth First Search) algorithm. Which serves to assist the community in conducting consultations without having to meet a disease expert or wait for counseling. Keywords : Expert system, Certainty factor, Breadth fisrt search, Chili plants